Pilot of a team-based quality improvement strategy to improve cardiovascular risk factors care in community mental health centers - Murphy, Karly A.; Gennusa, Joseph; Dalcin, Arlene T.; Cook, Courtney; Goldsholl, Stacy; Fink, Tyler; Daumit, Gail L.; Wang, Nae-Yuh; Thompson, David; McGinty, Emma E. (Frontiers in Psychiatry, 2025)
IntroductionPopulations with serious mental illness are less likely to receive evidence-based care for cardiovascular disease (CVD) risk factors. We sought to characterize the implementation of an adapted team-based quality improvement strategy to improve mental health providers’ delivery of evidence-based CVD risk factor care.MethodsIn a 12-month, single arm pre/post pilot study in four behavioral health homes embedded within psychiatric rehabilitation programs, sites implemented an adapted Comprehensive Unit Safety Program (CUSP). Primary measures examined changes in organizational quality improvement culture and provider self-efficacy for CVD risk factor care. Secondary measures examined changes in acceptability, appropriateness, and feasibility of CUSP and receipt of guideline-concordant care for hypertension, dyslipidemia, and diabetes.ResultsProvider self-efficacy to coordinate care for hypertension and diabetes improved, but organizational quality improvement culture did not change. Acceptability, appropriateness, and feasibility were rated highly but did not change pre/post CUSP. The percentage who reached goals per national guidelines improved for those with dyslipidemia but not for those with hypertension or diabetes. CUSP teams implemented processes to build staff capacity, standardize communication, elicit feedback, and deliver education on coordination for CVD risk factors.ConclusionThis pilot study showed no effects of CUSP on organizational quality improvement culture or provider self-efficacy, the mechanisms by which CUSP is expected to improve care processes. Long term investments are needed to support organizational quality improvement work and providers’ efficacy to delivery - evidence-based CVD risk factor care delivery.Clinical Trial Registrationhttp://www.ClinicalTrials.gov, identifier NCT04696653.